The Ravidassia in Italy: History, Geography, and Identity Politics of the Largest Punjabi Dalit Diaspora in the EU - Annamaria Laudini (Religions, 2025)
This article discusses caste dynamics within the Punjabi diaspora in Italy—the largest in the EU—by focusing on the case of the Ravidassia community and describing its evolving relations with the local Sikh community. Previous research on Punjabi migration to Italy mainly focused on issues of labor exploitation, intermediation, and Sikh identity, often conflating the entire Punjabi population with its majoritarian—but far from exclusive—Sikh-Jatt component, thereby overlooking its internal heterogeneity of caste, religion, and class. Despite the growing number of Ravidassia-Chamar migrants in Italy—evidenced by the proliferation of Ravidassia temples and associations across the country—their migratory experiences, employment patterns, socioreligious practices, and inter-caste relationships remained unexplored. This article offers, for the first time, an overview of the history, geography, and identity politics of the Ravidassia in Italy. Drawing on data collected with Punjabi migrants during multi-sited ethnographic fieldwork, it illustrates the alternative strategies adopted by the Ravidassia to assert their identity in this diasporic context, focusing on cases in which their relations with the Sikh manifested their complex nature. It concludes by discussing the advantages and drawbacks of each strategy, in light of the history of power relations between the Ravidassia and the Sikh.